1999
DOI: 10.1111/j.1745-4514.1999.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERIZATION OF PROTEOLYTIC ACTIVITY IN OCTOPUS (Octopus vulgaris) ARM MUSCLE

Abstract: A new proteolytic activity assay was devised to avoid the interference of paramyosin which causes gelling during the enzymatic assay. Extremely high autolytic activity was observed in octopus arm muscle, which was 40–500 fold higher than those of various other fish species. The proteinase was inhibited strongly by leupeptin and iodoacetic acid and, to a lesser degree, by transepoxysuccinyl‐L‐leucylamino (4‐guanidono)butane (E‐64), indicating the class as a thioi proteinase. The proteinase exhibited optimum act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
2
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
(21 reference statements)
3
41
2
4
Order By: Relevance
“…Previous works have informed on the physico-chemical, biochemical, and functional properties of major myofibrillar proteins from squid Illexargentinus (Paredi, Roldán, & Crupkin, 2006;Mignino & Paredi, 2006). It had been also reported that, cephalopods have peculiarities of proteins and high level of proteolytic activity, higher than that of most fish species (Hurtado, Borderías, Montero, & An, 1999). Moreover, it has been reported that some of the proteases involved in that proteolytic activity, have as target the myosin heavy chain (MHC) producing degradation of the same (Konno & Fukazawa, 1993;Konno, Yuong-Je, Yoshioka, Shinhho, & Seki, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have informed on the physico-chemical, biochemical, and functional properties of major myofibrillar proteins from squid Illexargentinus (Paredi, Roldán, & Crupkin, 2006;Mignino & Paredi, 2006). It had been also reported that, cephalopods have peculiarities of proteins and high level of proteolytic activity, higher than that of most fish species (Hurtado, Borderías, Montero, & An, 1999). Moreover, it has been reported that some of the proteases involved in that proteolytic activity, have as target the myosin heavy chain (MHC) producing degradation of the same (Konno & Fukazawa, 1993;Konno, Yuong-Je, Yoshioka, Shinhho, & Seki, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous proteases play an important role in softening of cephalopod tissue, including octopus (Hurtado et al 1999;Hatate et al 2000). The cornea was initially tranluscent which became slightly opalescent on day 2 and completely opalescent from day 5 onwards.…”
Section: Sensory Qualitymentioning
confidence: 99%
“…This result clearly demonstrated that the spoilage of octopus was mainly autolytic and not microbial. Hurtado et al (1999) also stated autolysis was more intense in octopus than microbial action. The total aerobic plate count at the point of rejection of fish products is usually log 7-9 CFU/g (Huss et al 1997;Olafsdottir et al 1997) and such higher counts were not obtained even on the day of rejection in the iced octopus.…”
Section: Bacteriological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hurtado et al (1999) reported a shelf life lasting 6 to 7 days after catch at 2.5°C and Barbosa and Vaz-Pires (2003) found a shelf life of 10 days at 0°C. Different methods and different parameters have been tested for monitoring quality and quality evolution during the shelf life, based on physical, chemical, and microbiological analysis.…”
Section: Qualitymentioning
confidence: 99%